Jonathan Livingston Seagull - Bach, Richard; Munson, Russell; Rouben Mamoulian Collection (Library of Congress) (New York : SCRIBNER, 1970)
Because he spends so much time perfecting his flying form instead of concentrating on getting food, a seagull is ostracized by the rest of the flock.
Keywords: Gulls -- Fiction